Customer satisfaction index in Indonesian student micro credentials program - Bismala, Lila; Siregar, Gustina; Andriany, Dewi; Handayani, Susi; Hafsah, Hafsah; Hasibuan, Lailan Safina; Arda, Mutia; Putra, Yudha Andriansyah; Manurung, Yayuk Hayulina (Intelektual Pustaka Media Utama, 2024)
The Indonesian Student Micro-Credentials Program implemented by Universitas Muhammadiyah Sumatera Utara (UMSU) carries 5 courses, all of which are carried out online, in a relatively short time within 2 months. The learning objectives, which are intended to create practical skills, require students to master the courses they follow, thus causing many problems, which have an impact on the satisfaction of the participants of this program. This study aims to measure the customer satisfaction index (CSI) of participants in this program. Of the 514 participants who were used as respondents, 279 respondents filled out the google formula, and the response rate was 54%. The results showed that the CSI value of the program was 0.85, which means that the participants were very satisfied with the implementation of this program at UMSU. Based on the assessment of it is quality, the dimension assessment is carried out in order of the highest average value, namely this program (4.48), interaction and flexibility (4.33), managers (4.24), lecturers (4.23), students (4.20), assessment (4.16), process (4.14), content design (4.15), partners (4.11), and technology (4.05). Based on the assessment of the level of importance or expectation of this program, the dimension assessment is carried out in order of the highest average value, namely this program (4.47), interaction and flexibility (4.38), managers (4.23), lecturers (4.22), process (4.17), content design (4.17), students (4.13), peer (4.13), assessment (4.11) and technology (4.04).